SYSTEMS FOR CONTROLLING THE RADIAL DIMENSION OF THE HONING FOR MACHINING SMALL DIAMETERS - SHCHERBYNA, KYRYL; TORCHILOV, DANYLO; ZAIKA, ANDRII; MANDZIUK, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Improvements in the functional parameters of machines, mechanisms, and technological equipment that are widely used in contemporary mechanical engineering are to a significant extent determined by the optimisation of finishing operations applied to precision parts. These operations critically influence the operational reliability and durability of mechanical systems. In particular, one of the decisive factors for enhancing the efficiency of hydraulic machines and the fuel systems of internal combustion engines is the high manufacturing quality of control equipment components. Among the key indicators of such quality are the parameters of surface roughness and the degree of macro-irregularities of working surfaces, as they have a direct impact on hydrodynamic characteristics, wear resistance, sealing performance of mating connections, and ultimately on the energy efficiency of fluid systems.Achieving the required precision and surface integrity during the final stages of hole machining is ensured through the honing process. Honing distinguishes itself by its unique capability to combine high dimensional accuracy with the ability to compensate for and correct geometric deviations of the workpiece surface. Its technological flexibility arises from the capacity to adapt machining modes dynamically to the actual shape errors of the hole, which enables the minimisation of residual defects without a significant increase in operational complexity or labour intensity. As a result, honing remains one of the most effective finishing methods for critical cylindrical surfaces in hydraulic and fuel control equipment.The article presents an in-depth scientific and technical analysis of a hydrostatic honing tool intended for high-precision machining of small-diameter holes. Special emphasis is placed on the distinctive features of its structural design, which ensure uniform pressure distribution in the contact zone between the tool and the workpiece, leading to enhanced stability of the cutting process and improved repeatability of machining results. A mathematical model describing the static equilibrium of the hydrostatic honing tool has been developed and validated using numerical simulation methods. This model makes it possible to assess the influence of design parameters and technological modes on the pressure field and on the behaviour of the cutting elements during operation.Particular attention is devoted to systematising the principal advantages of hydrostatic honing tools compared to conventional designs. These include increased stability of the machining process due to the absence of mechanical deformation elements, reduced tool wear owing to optimised load distribution, and enhanced surface quality of the finished parts. At the same time, the research identifies specific design and technological constraints, such as limitations in minimum hole diameter, sensitivity to fluid cleanliness, and the need for precise control of hydrostatic pressure. The obtained results provide a theoretical and practical basis for improving the efficiency of honing operations in precision engineering, particularly for components of hydraulic and fuel control systems that require exceptional accuracy and surface integrity.
Keywords: honing head; hydrostatic honing; radial size control system; elastic deformation; elastically deformable shell; small displacement zone